The End is Not the Injury: Posttraumatic Growth After Sport Injuries - Vann, Sasa Elizabeth; Moore, Dr. Matthew; Freiburger, Kelsey; Johnson, Hannah (Journal of Amateur Sport, 2019)
This quantitative study explored whether serious injuries in varsity high school or collegiate athletes could produce Posttraumatic Growth (PTG). The impact of injury (season- or career-ending) and an athlete’s highest level of competition played (varsity high school or collegiate) were examined on five elements on the 2-item Posttraumatic Growth Inventory (PTGI): (1) relating to others, (2) new possibilities, (3) personal strength, (4) spiritual change, and (5) appreciation of life. This study provides evidence that sport level does not impact an athlete’s ability to produce PTG and bring awareness to trauma and the role PTG can have in an athlete’s life.